Comparative RFLP Mapping of a Wild Rice, Oryza officinalis, and Cultivated Rice, O. sativa. - Jena, K.K.; Khush, G.S.; Kochert, G. (Canadian Science Publishing, 1994)
A comparative RFLP map was constructed in a wild rice, Oryza officinalis, by using 139 genomic and cDNA probes that had been used previously to map RFLPs in O. sativa. Nine of the 12 chromosomes of O. officinalis were highly homosequential to those of O. sativa. A major rearrangement of gene order was detected in chromosome 1 and small inversions were found in chromosomes 3 and 11. Fourteen translocated RFLP markers were found, and chromosome 11 contained a high frequency of such translocated segments. Results were consistent with meiotic and trisomie analysis, which suggested that the genomes of O. officinalis and O. sativa were similar. Applications of comparative maps in plant breeding and gene cloning are discussed.Key words: Oryza, rice, wild rice, RFLP, genetic map.